A Decline in 2 Consecutive Postmortem Serum Tryptase Levels in an Anaphylactic Death. (December 2015) - Sravan, Anne; Tse, Rexson; Cala, Allan David
Abstract : Abstract: The diagnosis of anaphylaxis in the postmortem setting remains a significant challenge for pathologists. The performance of postmortem serum tryptase is commonly used in the investigation of suspected anaphylactic deaths; however, not only have tryptase levels been found to be elevated in nonanaphylactic deaths, the effect of the postmortem interval on serum tryptase is not fully understood. There are no studies on serial measurement of tryptase in the postmortem setting. We report a death from anaphylaxis in which 2 separate serum tryptase measurements taken 24 hours apart from the same femoral vein showed a substantial decline from 130.0 ug/L at day 2 after death to 84.4 ug/L at day 3. We hypothesize that the decline may be due to degradation of the degranulated mast cell tryptase in anaphylactic deaths. Serial measurement of postmortem serum tryptase may assist in understanding the complex field of serum tryptase interpretation in the postmortem setting. We suggest that an early blood sample to be obtained as soon as possible after death in cases where anaphylaxis is suspected, because there appears to be a significant decline in tryptase levels with increasing postmortem interval.